Demolition of a 65-year-old box-girder prestressed concrete bridge located in Northern Sweden - Daescu, Cosmin Al; Gonzalez-Libreros, Jaime; Wang, Chao; Elfgren, Lennart; Sas, Gabriel (ce/papers, 2023)
A new bridge was built in Kalix, northern Sweden, to replace an existing prestressed concrete box-girder bridge that had been in service for over 60 years. The old bridge had a total length of 283.6 m divided into five spans: 43.9 m, 47.0 m, 94.0 m, 47.0 m, and 43.9 m. It was constructed using the balanced cantilever method with segments having lengths of around 3.0 m. The need for replacement arose from recommendations extracted from an assessment of the old bridge's state and capacity. In addition to the construction of the new bridge, its replacement necessitated the creation and evaluation of demolition procedure for the existing bridge. This procedure had to be carefully designed to avoid damaging the new bridge and stability-related issues but also to prevent debris from falling into the Kalix River, which is part of a Natura 2000 protected area. This paper discusses various issues considered while developing the demolition strategy, including the use of bed-rock anchored tendons, intermediate support fixing at specific locations, and proper evaluation of position of the demolition equipment supported by the bridge, among others. The problem of disposing of the demolished material is also discussed. Funder: NCC Infrastructure, Civil Engineering Division, Sweden; Full text license: CC BY